8. CLINICAL MANIFESTATIONS, LABORATORY FINDINGS ON PATIENTS WITH DEMODICOSIS (Vietnam Journal of Community Medicine, 2024)
Objectives:To describe of clinical manifestations, laboratory findings of demodicosis patients.Methods: A cross-sectional study design.Results: In total of 93 enrolled demodicosis patients, the basic lesions composed ofpustules 38 cases(40.9%), skin rash 29 (31.2%), skin scales 59 (63.4%), papules 22 (23,7%). Diverse symptomes composed of itching 81 (87.1%), stinging 73 (78.5%), crawling ants 78 (83.9%), alopecia 3 (3.2%) and eyelash and eyebrow loss 1 (1.1%). Most lesions focused on cheeks, chin, neck, ears 84 (90.3%), chest and shouder back 7 (7.5%), blepharitis 2 (2.2%). The rosacea-like type was highest proportion 45 (48.4%), papulal seborrheic dermatitis type 31 (33.3%), pityriasis folliculorum type 24 (25.6%), granulomatous rosacea-like type 8 (8.6%). Most of them were mild, and moderate demodicosis with 48 (51.6%) and 42 (45.2%), respectively. Under microscopy, mean Demodex spp. density of in range (>5-
Keywords: Demodicosis; Demodex spp. mites; rosacea-like skin lesions